Immune and genetic mechanism of hepatitis C virus persistence after mother-to-child transmission (Review of English language publications) - Yu. V. Lobzin; D. A. Gusev; A. A. Lutckiy (Журнал инфектологии, 2014)
Chronic viral hepatitis C is one of the major health challenges in the present decade. Every year about 3–4 million of newly infected patients added to reservoir of infection that according to the experts estimates contain more than 170 million of individuals. After introduction of the routine blood products screening for hepatitis C virus, mother-to-child transmission became the major source of hepatitis C infection in childhood. This review represent the modern understanding of the genetic and immune mechanism of hepatitis C virus persistence after mother-to-child transmission, development of innate chronic hepatitis C, current practices and perspectives for its prevention presented in English language sources of scientific information.